2010
DOI: 10.2134/agronj2009.0337
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Response in Conventional and Glyphosate Resistant Soybean

Abstract: Fertilizer Management 606A gronomy J our n al • Volu me 102 , I s sue 2 • 2 010 ABSTRACT Glyphosate-resistant (GR) soybean [Glycine max (L.) Merr.] is widely produced and provides many benefi ts to production agriculture, however, recent reports suggest that GR soybean genetics may result in reduced Mn uptake and increased response to Mn fertilization. Th e objective of this research was to determine response of GR and conventional (CV) soybean near-isolines to Mn fertilization. Th e soybean near-isoline pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
2
18
0
7
Order By: Relevance
“…Corroborando assim com Lavres Júnior et al (2008) De modo geral, com aplicação realizada em R 1 ou em R 3 , quando as cultivares foram distintas, os materiais convencionais foram mais produtivos em relação aos seus derivados transgênicos RR, tanto na ausência quanto na aplicação do Mn foliar (Tabela 4). Corroborando com os resultados obtidos por Loecker et al (2010), que constataram que a transgenia RR não proporcionou conclusivamente em maior resposta à aplicação de Mn.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Corroborando assim com Lavres Júnior et al (2008) De modo geral, com aplicação realizada em R 1 ou em R 3 , quando as cultivares foram distintas, os materiais convencionais foram mais produtivos em relação aos seus derivados transgênicos RR, tanto na ausência quanto na aplicação do Mn foliar (Tabela 4). Corroborando com os resultados obtidos por Loecker et al (2010), que constataram que a transgenia RR não proporcionou conclusivamente em maior resposta à aplicação de Mn.…”
Section: Resultsunclassified
“…Existem algumas explicações teóricas que podem sustentar estas alegações, que geralmente estão na direção de dois mecanismos gerais: (i) interação direta ou indireta entre glifosato e Mn, ou, (ii) diminuição na absorção e translocação de Mn resultante da alteração genética (LOECKER et al, 2010).…”
Section: Introductionunclassified
“…In the early adoption stage of TCs, transgenic crops with IR traits usually yielded similar to near-isolines (Baute et al, 2002;Cox and Cherney, 2001;Dillehay et al, 2004;Traore et al, 2000), suggesting that the insertion of an IR gene in the early IR crops did not provide higher yield. However, some of the first transgenic crops with GR traits provide the same or even lower yield on average than conventional varieties due to the introduction of the GR gene into varieties with lower yield potential (Elmore et al, 2001;Heatherly et al, 2002 andLoecker et al, 2010;Shaw et al, 2001). However, transgenic traits were later introduced into improved potential yield varieties and generally showed that transgenic hybrids produced similar or higher yields than conventional varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies were conducted in greenhouse and have been used as support for claims of decreased yields and other adverse effects of glyphosate on GR crops (e.g., Huber, 2007;Johal and Huber, 2009). Other research groups have found no effects of glyphosate on mineral nutrition in GR crops (e.g., Bailey et al, 2002;de Andrade and Rosolem, 2011;Duke et al, 2012a;Henry et al, 2011;Loecker et al, 2010;Rosolem et al, 2010;Serra et al, 2011). A thorough analysis of this topic was made by Duke et al (2012b).…”
Section: Glyphosate-resistant Crops and Mineral Nutritionmentioning
confidence: 95%